Усні джерела Галицько-волинського літопису - Кирієнко, Г. (Народна творчість та етнографія, 2008)
The author focuses on the verbal sources of Halytsko-Volynsky Litopys (The Chronicle of Halytsko-Volynsky Principality). Using methods of V. Propp and other researchers, the author analyses specific structural and stylistic elements of the tale, which are present in the chronicle and got corresponding interpretation.